2007
DOI: 10.1002/mds.21509
|View full text |Cite
|
Sign up to set email alerts
|

Cued task‐specific training is better than exercise in improving sit‐to‐stand in patients with Parkinson's disease: A randomized controlled trial

Abstract: We examined whether 4 weeks of audio-visual (AV) cued task-specific training could enhance sit-to-stand (STS) and whether the treatment effects could outlast the treatment period by 2 weeks. Fifty-two subjects with PD completed the study. They were randomly allocated to receive 4 weeks of AV cued task-specific training, conventional exercise (Ex), or no treatment (control). Each subject was assessed before, at the end of 2 and 4 weeks of treatment, and 2 weeks after treatment ended. After 2 weeks of training, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 40 publications
0
53
1
5
Order By: Relevance
“…A common feature of these studies deals with the introduction of enhanced sensory feedback (auditory, visual or somatosensory) cues to provide augmented feedback about performance. Motor learning is enhanced by external cueing [47] whilst clinical studies have shown that externally cued practice over more extended periods (3-6 weeks) leads to significant benefits for gait and balance [48][49][50] and is more effective than interventions that do not use augmented feedback [44,51].…”
Section: Feasibilitymentioning
confidence: 99%
“…A common feature of these studies deals with the introduction of enhanced sensory feedback (auditory, visual or somatosensory) cues to provide augmented feedback about performance. Motor learning is enhanced by external cueing [47] whilst clinical studies have shown that externally cued practice over more extended periods (3-6 weeks) leads to significant benefits for gait and balance [48][49][50] and is more effective than interventions that do not use augmented feedback [44,51].…”
Section: Feasibilitymentioning
confidence: 99%
“…Evidence indicates that task-specifi c training could have relevance for people affected by a traumatic brain injury (Canning et al, 2003;Chua et al, 2007), Parkinson's disease (Mak and Hui-Chan, 2008), a total hip replacement (Drabsch et al, 1998), a work-related injury (McCannon et al, 2005) and/or a spinal cord injury (Betker et al, 2007;Kubasak et al, 2008). However, most of the taskspecifi c training evidence relates to post-stroke recovery.…”
Section: Evidence For Task-specifi C Training In Rehabilitationmentioning
confidence: 99%
“…They can help PwP to ascertain their best cueing modality, frequency and timing for the situations in which they experience problems with initiating or maintaining movements. The effectiveness of cueing on gait (including turning) in PD is well-established, even in the patient's home environment, without increasing the risk for falls [94][95][96]. Rhythmic auditory cues even seem to reduce the interference effect of a dual task on gait [93,97].…”
Section: Movement Strategy Trainingmentioning
confidence: 99%